Predicting Online Purchase Intention on Marketplace - Wicaksono, Teguh; Syahrani; Purboyo; Abdurrahim (CV ODIS, 2023)
This study aims to explain the correlation between consumer trust and other factors that could increase the consumer's online purchase intention in the marketplace. This research uses quantitative methods and the data is collected from 138 respondents in Banjarmasin who had made online purchases, at least 2 times in the last 3 months, using a questionnaire. Then, the data is analyzed using PLS-SEM. The empirical result proves that consumer trust does not have a direct impact on online purchase intention, but the indirect effect of consumer trust has an impact on online purchase intention through attitude as an intervening variable. Information quality directly has an impact on online purchase intention, but consumer trust as an intervening variable of information quality indirectly does not have an impact on online purchase intention. Those results show that most consumers purchase online to acquire the needed products or services. Therefore, they are more concerned with the benefits and conveniences obtained from online purchasing. Trust is no longer the main factor affecting online purchase intention. To increase online purchase intention, online merchants should provide the best information quality related to the offered products and services and provide a sense of comfort and convenience to consumers in making transactions.